2019
DOI: 10.25259/apos_123_2019
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in orthodontics

Abstract: This article aims to discuss how AI with its powerful pattern finding and prediction algorithms are helping orthodontics. Much remains to be done to help patients and clinicians make better treatment decisions. AI is an excellent tool to help orthodontists to choose the best way to move teeth with aligners to preset positions. On the other hand, AI today completely ignores the existence of oral diseases, does not fully integrate facial analysis in its algorithms, and is unable to consider the impact of functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The applications of AI programs in dentistry are very interesting and sustainable, especially in radiology (2)(3)(4)(5)(6)(7)(8)(9). In recent years, AI applications in dentistry have attracted attention in areas ranging from the diagnosis of caries to the detection of various pathologies, from planning orthodontic treatment of crowded teeth to robotic surgery and dental implant construction (10)(11)(12)(13). Especially adaptation with image processing methods has highlighted the studies of dental radiology.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of AI programs in dentistry are very interesting and sustainable, especially in radiology (2)(3)(4)(5)(6)(7)(8)(9). In recent years, AI applications in dentistry have attracted attention in areas ranging from the diagnosis of caries to the detection of various pathologies, from planning orthodontic treatment of crowded teeth to robotic surgery and dental implant construction (10)(11)(12)(13). Especially adaptation with image processing methods has highlighted the studies of dental radiology.…”
Section: Introductionmentioning
confidence: 99%
“…[39] ese AI-based system assists orthodontists to determine orthodontic tooth movement but there are several limitations of ML in traditional clear aligner therapy. [40] Another limitation of the system is that they do not involve the importance of facial analysis, their proportions, and the esthetics of individuals. [41,42] Neural networks were also used to estimate the dental ages of the patient from panoramic radiographs.…”
Section: Ai For Orthodontic Diagnosis and Treatment Planningmentioning
confidence: 99%
“…Artificial intelligence does not necessarily mimic the human brain, it is rather a problem-solving tool which has its own set of rules. Studies have been conducted to achieve human-like behaviors with AI and it has been found that computers exceed human results in many parameters (Faber et al, 2019). Artificial intelligence technology has been used in a wide spectrum from differential diagnosis and radiographic interpretation to restorative treatment in dental field (Khanna, 2010).…”
Section: Artificial Intelligence Which Was Brought Forward Bymentioning
confidence: 99%